ETNOGRAFI KOMUNIKASI UPACARA HARI RAYA GALUNGAN DI KEPENGHULUAN PASIR PUTIH KECAMATAN BALAI JAYA KABUPATEN ROKAN HILIR PROVINSI RIAU - Oktavia, Frida; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
ceremony is one of the rituals performed to celebrate the dharma victory (goodness) against adharma (evil) and as a form of gratitude to God Almighty. Ceremony of this galungan feast is also done by presenting banten that has been prepared by the people of bali villages and held this ceremony also to keep the rope silahturahmi between the people of Bali tribe in Kepenghuluan Pasir Putih with other communities. The purpose of this study to know the communicative situation, communicative events, and communicative acts in ceremonies Galungan feast in Kepenghuluan PasirPutih.The research method used is qualitative method by using ethnographic approach of communication. Informants in this study were 5 persons consisting of one person with adat stakeholder status, one person with status of community leader, one person with status of temple chairman, and two people with community status. And data collection technique using snowball sampling technique after that done participant observation, depth interview, and documentation.Based on the results of this study obtained shows that the communicative situation occurred in Pura Ganathana Kepenghuluan Pasir Putih and attended by the people of Bali and other communities. Communicative events in galungan ceremony consists of the type of event that is the opening greetings from the adat and community stakeholders and accompanied by the sound of bells. Topics in the form of a sign of gratitude. Purpose and function to request a prayer to Hyang Widhi. Setting is a ceremony held on the day around 10:00 pm until finished. Participants are family and society. The forms of messages are verbal and nonverbal. The contents of his message was begging for purgation and thankfulness. The sequence of action is to prepare a sitting posture, praying prayer, praying, mentirtha.The rules of interaction are found when the adat stakeholders begin the ceremony, at the mentirtha, discourse, and visit. The norms of interpretation there are values of decency, solidarity, and values of obedience and obedience to religion and custom. Communicative acts in the ceremony of Galungan festivities in the form of people who know the norms and have the skills in undergoing a series of ceremonies of Galungan.